How you look is who you are: The appearance reveals character lay theory increases support for facial profiling - MADAN, Shilpa (Institutional Knowledge at Singapore Management University, 2022)
People are excessively confident that they can judge others’ characteristics from their appearance. This research identifies a novel antecedent of this phenomenon. Ten studies (N = 2,967, 4 preregistered) find that the more people believe that appearance reveals character, the more confident they are in their appearance-based judgments, and therefore, the more they support the use of facial profiling technologies in law enforcement, education, and business. Specifically, people who believe that appearance reveals character support the use of facial profiling in general (Studies 1a and 1b), and even when they themselves are the target of profiling (Studies 1c and 1d). Experimentally inducing people to believe that appearance reveals character increases their support for facial profiling (Study 2), because it increases their confidence in the ability to make appearance-based judgments (Study 3). An intervention that undermines people’s confidence in their appearance-based judgments reduces their support for facial profiling (Study 4). The relationship between the lay theory and support for facial profiling is weaker among people with a growth mindset about personality, as facial profiling presumes a relatively unchanging character (Study 5a). This relationship is also weaker among people who believe in free will, as facial profiling presumes that individuals have limited free will (Study 5b). The appearance reveals character lay theory is a stronger predictor of support for profiling than analogous beliefs in other domains, such as the belief that Facebook likes reveal personality (Study 6). These findings identify a novel lay theory that underpins people’s meta-cognitions about their confidence in appearance-related judgments and their policy positions.